THE SIGNIFICANCE OF INTERNATIONAL HUMANITARIAN LAW IN SAFEGUARDING THE ENVIRONMENT IN ARMED CONFLICT ZONES - Singh, Priyanka; Sharma, Chandrika Setu; Mishra, Kriti; Goel, Anjanee; Kajal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The primary motivation behind the researchers’ writing of this work is the fundamental need for human safety and care for survival at all times. Man is the essence of existence, and his sense of safety and tranquillity, which ensures his liberties and his dignity at all times, are the foundations of his survival. Because international humanitarian law is intimately related to human rights, it is one of the most significant areas of international public law, and its provisions reflect the expansion of human rights. As long as they follow this law’s guidelines and provisions, it has so far saved millions of lives. This paper aims to determine the extent to which International Humanitarian Law contributes to the safeguarding of the ecosystem. This will be achieved by examining existing studies and assessing conferences, conventions, and international agreements that address international humanitarian law.